An Autoethnographic Story of Abuse: Healing and Finding Hope Through a Sexual Health Promotion Project for Adolescents With Developmental Disabilities. Issue 4 (October 2016) - Murray, B. Lee
Abstract : ABSTRACT: This case report is the story of my son's alleged abuse, told from my perspective. At the time, Jordan, a boy with Down syndrome, was 14 years old when his disclosure of sexual abuse by a school employee occurred. As part of the healing process, I use autoethnography to tell the story. I also describe and discuss a school-based program, which I developed and deliver, to provide sexual health promotion and sexual abuse prevention to adolescents with developmental disabilities.